The pelagic squid assemblage of the Kerguelen Axis - Lin, D; Trebilco, R; Walters, A; Zhu, G; Chen, X (Australian Antarctic Division, 2019)
Squids are increasingly acknowledged as an ecologically important group in SouthernOcean ecosystems, and most are represented exclusively by endemic species due tothe biological barrier of Antarctic Polar Front. However, there are still large gaps intheir now-known biogeographic components, especially the population diversity in theIndian sector. We thus present a first evaluation of diversity and distribution of the squidpopulations in the Kerguelen Plateau, based on an ecosystem study of the Kerguelen Axisconducted between January and February 2016. A total of 801 squid specimens werecollected from 36 stations, at depths from the surface to 1 000 m and were identifiedto seven species from six families, including Alluroteuthis antarcticus, Bathyteuthisabyssicola, Galiteuthis glacialis, Mastigoteuthis psychrophila, Mesonychoteuthishamiltoni, Psychroteuthis glacialis and Slosarczykovia circumantarctica . Speciescomposition was dominated by G. glacialis and P. glacialis , which accounted for 68.79%and 11.24% of the total collection respectively. We examined geographic niche breadthof these species in terms of their distributions across stations and with depth. All of thesespecies exhibited a broad niche breadth, being the Shannon-Wieners niche breadth index(B i ) from 1.91 to 8.43. Variations of diversity index were estimated in a range of 0.39to 1.56, and most of the peak diversity stations were found at the short deep-sea slope areaand deep-sea basin. This variation was consistent with the bathymetric gradient of depth,although the relationship was not statistically significant. In addition, the highest diversitywas detected in the top 200 m of the water column, with an occurrence >50% for mostspecies at this depth stratum. This study demonstrates the squids population diversity inthe southern Kerguelen Plateau, with new insights into their endemicity and diversity inthis biologically important area.